Development of Local Wisdom-Based Edugames in the PKn Subject of Grade V State Elementary School 101871 Sidodadi Village - Amirah Fadhil Ramadhaini Nasution (Journal of Elementary School Education, 2025)
This study aims to develop a learning media in the form of a local wisdom–based educational game (edugame) for Civic Education (PKn) in Grade V at SD Negeri 101871 Sidodadi Village, as well as to determine the validity and practicality levels of the developed media. This study employed a Research and Development (R&D) method using the 4D development model, which includes the stages of define, design, development, and disseminate. However, this research was conducted only up to the development stage. The results showed that the developed edugame fell into the very valid category, with validation percentages of 84% from the material expert, 100% from the media expert, and 100% from the language expert. In addition, the practicality test results indicated that the media was categorized as very practical, with a teacher response percentage of 100% and a student response percentage of 90.30%. These findings indicate that the developed edugame is easy to use, engaging, and capable of increasing student involvement in the learning process. Therefore, the locally developed wisdom–based edugame is considered feasible and practical to be used as a learning media for Civic Education in elementary schools, and it supports more interactive, contextual, and meaningful learning for students.